THE INFLUENCE OF MOTIVATION AND WORK COMMUNICATION ON EMPLOYEE PERFOMANCE AT PT.INTI TERANG SUKSES WITH WORK SPIRIT AS INTERVENING VARIABLES - Yenni Mariani Sinurat; Yenni Arfah; Cindy Milenia Winar (RADJA PUBLIKA, 2023)
The purpose of this study is to examine the effect of (1) motivation on employee performance (2) work communication on employee performance (3) motivation on work spirit (4) work communication on work spirit (5) motivation on employee performance through work motivation as an intervening variable (6) work communication on employee performance through work motivation as an intervening variable (7) work spirit on employee performance. This study uses a quantitative research approach with the type of explanatory research which aims to analyze how the relationship between one variable with another variable. The population in this study were all of the employees of PT Inti Terang Sukses total of 35 employees. This study uses saturated sampling technique which made all of the population member as the sampel of this study. Questioner was used in this study as the method of collecting data. Analysis tools: instrument test, classical assumption test, multiple linear regression analysis, t test and path analysis using SPSS version 25. The result from this study indicates that motivation affect employee performance, work communication does not affect employee performance and, motivation and work communication affect motivation, and based on the result of path analysis shows that work spirit cannot mediate the effect of motivation on employee performance but can mediate the effect of work communication on employee performance and work spirit affect employee performance.